Treatment of pediatric convulsive status epilepticus - Becker, Lena-Luise; Gratopp, Alexander; Prager, Christine; Elger, Christian E.; Kaindl, Angela M. (Frontiers in Neurology, 2023)
Status epilepticus is one of the most common life-threatening neurological emergencies in childhood with the highest incidence in the first five years of life and high mortality and morbidity rates. Although it is known, that a delayed treatment and a prolonged seizure can cause permanent brain damage, currently there is evidence that treatment may be delayed and medication doses administered are insufficient. Here, we summarize current knowledge on treatment of a convulsive status epilepticus in childhood and propose a treatment algorithm. We performed a structured literature search via Pubmed and ClinicalTrails.org and identified 35 prospective and retrospective studies on children < 18 years comparing two and more treatment options for status epilepticus. The studies were divided into the commonly used treatment phases. As a first line treatment benzodiazepines buccal/rectal/intramuscular/intravenous are recommended. For benzodiazepine refractory status epilepticus no superiority of fosphenytoin, levetirazetam, or phenobarbital was identified. There is limited data on third-line treatments for refractory status epilepticus lasting > 30 min. Our proposed treatment algorithm especially for children with SE for in and out-of-hospital onset aids to promote the establishment and distribution of guidelines to address the treatment delay aggressively and to reduce putative permanent neuronal damage. Further studies are needed, to evaluate if these algorithms decrease long-term damage and how to treat refractory status epilepticus lasting > 30 min.